Impact of Thrombus Sidedness on Presentation and Outcomes of Patients with Proximal Lower Extremity Deep Vein Thrombosis - Bikdeli, Behnood; Sharif-Kashani, Babak; Bikdeli, Bavand; Valle, Reina; Falga, Conxita; Riera-Mestre, Antoni; Mazzolai, Lucia; Verhamme, Peter; Wells, Philip S.; Torrero, Juan Francisco Sánchez Muñoz; Lopez-Jiménez, Luciano; Monreal, Manuel; For the RIETE Investigators (Seminars in Thrombosis and Hemostasis, 2018)
Small studies have suggested differences in demographics and outcomes between left- and right-sided deep vein thrombosis (DVT), and also unilateral versus bilateral DVT. We investigated the clinical presentation and outcomes of patients with DVT based on thrombus sidedness. The authors used the data from the Registro Informatizado Enfermedad TromboEmbólica (RIETE) database (2001–2016) to identify patients with symptomatic proximal lower-extremity DVT. Main outcomes included cumulative 90-day symptomatic pulmonary embolism (PE) and 1-year mortality. Overall, 30,445 patients were included. The majority of DVTs occurred in the left leg (16,421 left-sided, 12,643 right-sided, and 1,390 bilateral; p < 0.001 for chi-squared test comparing all three groups). Comorbidities were relatively similar in those with left-sided and right-sided DVT. Compared with those with left-sided DVT, patients with right-sided DVT had higher relative frequency of PE (26% versus 23%, p < 0.001) and 1-year mortality (odds ratio [OR]: 1.08; 95% confidence interval [CI]: 1.00–1.18). This difference in mortality did not persist after multivariable adjustment (OR: 1.01; 95% CI: 0.93–1.1). Patients with bilateral DVT had a greater burden of comorbidities such as heart failure, and recent surgery compared with those with unilateral DVT (p < 0.001), and higher relative frequency of PE (48%), and 1-year mortality (24.1%). Worse outcomes in patients with bilateral DVT were attenuated but persisted after multivariable adjustment for demographics and risk factors (OR: 1.64; 95% CI: 1.43–1.87). Patients with bilateral DVT had worse outcomes during and after discontinuation of anticoagulation. There is a left-sided preponderance for proximal lower-extremity DVT. Compared with those with left-sided DVT, patients with right-sided DVT have slightly higher rates of PE. Bilateral DVT is associated with markedly worse short-term and 1-year outcomes.
Keywords: deep vein thrombosis; right; left; bilateral; pulmonary embolism